Structural and microstructural study of SnS thin film semiconductor of 0.2 - Ojonugwa Daniel, Thomas; Essang Uno, Uno; Uthman Isah, Kasim; Ahmadu, Umaru (International Journal of Physical Research, 2019)
SnS semiconductor thin film of 0.20, 0.25, 0.30, 0.35, 0.40 Î¼m were deposited using aerosol assisted chemical vapour deposition (AACV) on glass substrates and were investigated for use in a field effect transistor. Profilometry, X-ray diffraction, Scanning electron microscope and Energy dispersive X-ray spectroscopy were used to characterise the structural and microstructural properties of the SnS semiconductor. The SnS thin film was found to initially consist of a single crystal at thickness of 0.20 to 0.25Î¼m after which it becomes polycrystalline with an orthorhombic crystal structure consisting of Sn and S elements whose composition varied with increase in thickness. The SnS film of 0.4 Î¼m thickness shows a more uniform grain distribution and growth with a crystal size of 60.57 nm and grain size of 130.31 nm signifying an optimum for the as deposited SnS films as the larger grains reduces the number of grain boundaries and charge trap density hence allowing charge carriers to move freely in the lattice thereby causing a reduction in resistivity, increase in conductivity of the films and enhanced energy band gap which are essentially parameters for a semiconductor material for application in a field effect transistor.Â Â